Analyses the Average Pressure on Left Foot and Right Foot among the Rural and Urban Primary School Students of Haryana: A Comparative Study of Foot Pressure in Rural and Urban Primary School Students in Haryana (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Foot structure has a long established connection to foot function within the research field. For this study random sampling technique has been used for the collection of data. The researcher has selected total 1500 individuals as subjects (750 rural students and 750 urban students measured the Static Planter Foot Pressure (PFP) and Body Mass Index (BMI) The subjects were asked to stand on BTS P – Walk modular system (Pressure plate) and the data was recorded for 5 seconds. The F value was found to be 0.798, which is not found significant even at (P